Abundance, spatial distribution, and characteristics of microplastics in agricultural soils and their relationship with contributing factors. (15th February 2023) - Khan, Muhammad Amjad; Huang, Qing; Khan, Sardar; Wang, Qingqing; Huang, Jingjing; Fahad, Shah; Sajjad, Muhammad; Liu, Yin; Mašek, Ondřej; Li, Xiaohui; Wang, Junfeng; Song, Xiaomao
Abstract: Agro-ecosystem contamination with microplastics (MPs) is of great concern. However, limited research has been conducted on the agricultural soil of tropical regions. This paper investigated MPs in the agro-ecosystem of Hainan Island, China, as well as their relationships with plastic mulching, farming practices, and social and environmental factors. The concentration of MPs in the study area ranged from 2800 to 82500 particles/kg with a mean concentration of 15461.52 particles/kg. MPs with sizes between 20 and 200 μm had the highest abundance of 57.57%, fragment (58.16%) was the most predominant shape, while black (77.76%) was the most abundant MP colour. Polyethylene (PE) (71.04%) and polypropylene (PP) (19.83%) were the main types of polymers. The mean abundance of MPs was significantly positively correlated ( p <  0.01) with all sizes, temperature, and shapes except fibre, while weakly positively correlated with the population (p = 0.21), GDP (p = 0.33), and annual precipitation (p = 0.66). In conclusion, plastic mulching contributed to significant contamination of soil MPs in the study area, while environmental and social factors promoted soil MPs fragmentation. The current study results indicate serious contamination with MPs, which poses a concern regarding ecological and environmental safety. Graphical abstract: Image 1 Highlights: Abundance and spatial distribution of MPs were analyzed in agriculture soil. Most of the MPs in soil of Hainan were fragments and < 500 μm in size. PE was the most abundant polymer observed in the study area. MPs distribution was site specific with no strong relation with crops. Plastic mulching was the main source of MPs in soil.